1998
DOI: 10.1111/j.1439-0523.1998.tb01929.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Brazilian wheat cultivars for aluminium toxicity in acid soils

Abstract: Aluminium (Al) toxicity is an important limiting factor for wheat Triticum aestivum L. adaptation to acid soils in different regions of Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 11 publications
3
19
0
1
Order By: Relevance
“…Genetic analysis of various wheat genotypes collected worldwide revealed that Al 3+ tolerance might have originated independently in the USA, Brazil, and China (Hu et al, 2008;Raman et al, 2008). However, to date, only the Al-tolerant wheat lines in Brazil have been studied extensively (Berzonsky, 1992;Riede and Anderson, 1996;De Sousa, 1998;Ma et al, 2005). Thus far, only limited numbers of wheat lines from China have been evaluated for Al tolerance (Hu et al, 2008), although significant genetic variation in Al tolerance has occurred among wheat landraces and cultivars (Stodart et al, 2007;Zhou et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic analysis of various wheat genotypes collected worldwide revealed that Al 3+ tolerance might have originated independently in the USA, Brazil, and China (Hu et al, 2008;Raman et al, 2008). However, to date, only the Al-tolerant wheat lines in Brazil have been studied extensively (Berzonsky, 1992;Riede and Anderson, 1996;De Sousa, 1998;Ma et al, 2005). Thus far, only limited numbers of wheat lines from China have been evaluated for Al tolerance (Hu et al, 2008), although significant genetic variation in Al tolerance has occurred among wheat landraces and cultivars (Stodart et al, 2007;Zhou et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although some Al-tolerant wheat lines have been identified, additional Al-tolerant germplasms are required to improve modern wheat crops (Berzonsky, 1992;Riede and Anderson, 1996;De Sousa, 1998;Hu et al, 2008). One of the most important Al-tolerant genetic sources was traced to Brazil, where acidic soils are predominant in wheat cultivation zones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os genótipos foram testados em área de solo caracterizado como Latossolo Vermelho distrófico típico, textura argilosa (Streck, 2002) Sousa (1998), que classifica os genótipos com escala de notas de 0 a 5 em relação a tolerância/sensibilidade ao alumínio, em que: altamente resistente (0,50-0,80); resistente (0,81-1,50); moderadamente resistente (1,51-2,50), moderadamente suscetível (2,51-3,50); suscetível (3,51-4,50) e altamente suscetível (4,51-5,0). O critério dos escores utilizado foi: 0,5, altamente resistente; 1, resistente, plantas normais e vigorosas com perfilho abundante; 2, moderadamente resistente, plantas normais, levemente menos vigorosas e com menos perfilhos do que o grupo anterior; 3, moderadamente suscetíveis, desenvolvimento das plantas intermediário; 4, suscetíveis, plantas deficientes, sem perfilho; e 5, altamente suscetíveis, plantas mortas ou com desenvolvimento muito deficiente.…”
Section: Methodsunclassified
“…However, in Brazil, wheat lines were selected for their ability to grow in acid soils. The Toropi cultivar, released in 1965 (Sousa, 1998), is well known for its Al and low-P tolerance (Rosa & Camargo, 1990), which has been associated to the greater root volume produced by this cultivar (Wiethölter, 2004). Anahuac cultivar, on the other hand, is responsive to increasing P availability and is sensitive to low P.…”
Section: Introductionmentioning
confidence: 99%